Pengaruh Current Ratio Dan Debt To Asset Ratio Terhadap Return On Assets Pada Pt. Andira Agro Tbk (ANDI) Periode 2019-2024: Syahriani - Syahriani Syahriani (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2025)
AbstractThe purpose of this research is to examine the influence of the Current Ratio and Debt to Asset Ratio on Return On Assets in the Company. Current Ratio (CR) is a liquidity ratio that shows the extent to which current liabilities are covered by assets that are expected to be converted into cash in the near future. This Debt to Asset Ratio describes how much influence the company's debt has on asset management and how much the debt contributes to fundingassets. The sampling technique in this research is Purposive Sampling, the type of data used is secondary quantitative data. The data used was obtained from the summary of financial reports audited every quarter on theofficial websites of the Indonesia Stock Exchange and PT. Andira Agro Tbk during the period studied. The first data analysis techniques used are descriptive statistics, classical assumption tests, multiple linear regression analysis, then hypothesis testing with the t test, F test, and R2 test. The results of this research indicate that partially the Current Ratio has no effect on Return On Assets tcount 1,453 < ttable 1.720. And the significance level is 0.162 > 0.05. And the Debt to Asset Ratio has an effect on Return On Assets tcount -2,417< ttable -1.720 or 2,417 > 1.720 and sig < 0.05, namely 0.025 < 0.05. Simultaneously it was found that the Current Ratio and Debt to Asset Ratio had an effect on Return On Assets with a value of sig = 0.004 < 0.05, and Fcount 7,569 > Ftable 3.493. Keywords: Current Ratio, Debt to Asset Ratio, Return On Assets